Pengaruh Konsentrasi Perekat Tapioka terhadap Kualitas Obat Nyamuk Bakar Berbahan Baku Limbah Batang Singkong dan Ekstrak Biji Pala (Myristica Fragans Houtt) - Yuyun Ari Trisnawati (abe.fp.unila.ac.id, 2022)
Making mosquito coils requires cassava stem powder, nutmeg powder, and tapioca glue. The purpose of this study was to study the effect of tapioca glue concentration on the characteristics of mosquito coils. The research which was carried out with the concentration of cassava stem powder, nutmeg powder, and tapioca glue respectively as follows; a) 16.67%, 26.04%, 58.34%, b) 16%, 24%, 60%, c) 15.38%, 23.07%, 61.53%, d) 14.81 %, 22.23%, 62.9%, and e) 14.28%, 22.32%, 64.28%. This research was conducted to study physical characteristics (moisture content, density, shatter resistance index, combustion rate, smoke distribution, and organoleptic tests). The method used in this study was a completely randomized design measured using the Indonesian Industry Standard (SII) No. 1113-84. The results showed that the variation in the treatment of adding the amount of tapioca adhesive in the manufacture of mosquito coils had a very significant effect on moisture content, density, shatter resistance index, and duration of burning. Keywords: Cassava Stem Powder, Mosquito Coils, Nutmeg Powder, Organic Adhesive.